IMPLEMENTATION OF ETHNOSCIENCE BASED SCIENCE LEARNING: LITERATUR REVIEW - Safitri, Ulfa; Suryanti; Nadi Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The level of science literacy in Indonesia is at a low level based on the results of the PISA test in 2018. Science literacy is an ability that must be mastered in the 21st century. Science literacy can be developed through ethnoscience. Ethnoscience is the transformation of the science of society into scientific science. This research is a literature review research with 10 SINTA-indexed journals and 2 Scopus-indexed journals. This study discusses the implementation of ethnoscience in science learning. Science learning that implements ethnoscience can be through learning media both electronic and print, learning models, direct and indirect learning resources, learning tools, and a combination of learning models and media. Learning by narrating ethnoscience can make the learning process more active, more meaningful, students can think analytically, are contextual, and can increase science literacy.